Angiotensin-converting enzyme insertion/deletion gene polymorphism and the progression of cerebral microbleeds - Yoon, Cindy W.; Kim, Jonguk; Suh, Young Ju; Kim, Byeong C.; Youn, Young Chul; Jeong, Jee Hyang; Han, Hyun Jeong; Choi, Seong Hye (Frontiers in Neurology, 2023)
The angiotensin-converting enzyme (ACE) insertion (I)/deletion (D) polymorphism has been studied as a genetic candidate for cerebral small vessel disease (CSVD). However, no previous study has evaluated the relationship between the ACE I/D polymorphism and cerebral microbleed (CMB), an important CSVD marker. We evaluated the association between ACE I/D polymorphisms and 2-year changes in CMBs. The CHALLENGE (Comparison Study of Cilostazol and Aspirin on Changes in Volume of Cerebral Small Vessel Disease White Matter Changes) database was analyzed. Of 256 subjects, 186 participants who underwent a 2-year follow-up brain scan and ACE genotyping were included. A linear mixed effect model was used to compare the 2-year changes in the number of CMBs between the DD and combined ID/II genotypes. Among 186 patients included in this study, 24 (12.9%) had the DD genotype, 91 (48.9%) had the ID genotype, and 71 (38.2%) had the II genotype. Baseline clinical characteristics and CSVD markers were not different between the two groups except for the prevalence of hypertension (DD 66.7% vs. ID/II 84.6%; P = 0.04). A multivariate linear mixed-effects model showed that the DD carriers had a greater increase in total CMB counts than the ID/II carriers after adjusting for the baseline number of CMBs, age, sex, and hypertension (estimated mean of difference [standard error (SE)] = 1.33 [0.61]; P = 3 0.03). The progression of CMBs over 2 years was greater in the ACE DD carriers compared with the combined II/ID carriers.